Effects of Brain Tissue Mechanical and Fluid Transport Properties during Ischaemic Brain Oedema: A Poroelastic Finite Element Analysis - Mohd Jamil Mohamed, Mokhtarudin; Shabudin, Abbas; Payne, Stephen J. (IEEE, 2019)
Reperfusion after ischaemic stroke is risky as it can result in the formation of brain oedema and brain tissue swelling, which subsequently leads to brain herniation. Brain herniation is an undesirable condition that may affect brain functionality and fatality. A mathematical model based on poroelastic model has been previously developed to describe brain oedema formation. In that model, the brain tissue is assumed as a homogeneous isotropic material. In this paper, the effects of the brain mechanical and fluid transport properties on brain oedema progression are investigated by solving the model in a realistic brain geometry using finite element scheme. Four model parameters, namely brain tissue Young's modulus, Poisson's ratio, water permeability, and viscosity are varied so that their effect on brain oedema formation can be investigated. The results show that the brain Young's modulus and Poisson's ratio play more important role in brain oedema formation compared to the water permeability and viscosity, when varying within certain limits. From these findings, the brain tissue mechanical properties must be optimized so that the model can be used extensively for patient-specific brain oedema progression prediction.